Pragma-Stylistic Analysis of Rhetorical Questions in some Selected Poems of Aƙilu Aliyu - Garba, Salisu (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
The uniqueness of Akilu’s poetry is in his dexterous manipulation and stylistic usage of language to convey his massage across the target readers. The aim of this paper is to examine the stylistic usage of interrogatives as rhetorical questions and persuasive techniques with the view of evaluating the effectiveness of the devices deployed by the artist. The paper thus tries to assert that, style makes or mars poetry. The selected poems are from the collection of Fasaha Akiliya (1978) and they include: Kalubale(Kbl), Daddaɗan daɗi Saniya (Dds), Kadaura (Kdr), Dan daudu (Ddu), Duniya Rawar ‘Yan mata (Dry), Kasaitaccen Gari Legas (Kgl), Hausa Mai Ban Haushi (Hbh) and Isra’i (Iri). The English renditions were mainly adopted from Muhammad (1977) and the efforts of the researcher. The paper thus, using rhetorical criticism, illustrates its focus through twenty rhetorical questions employed as persuasive devices which are aesthetically and effectively used by the poet in the corpus. The paper, further showcases that, all the rhetorical questions are semantically declaratives and assertive. The paper hence concludes that, all the persuasive techniques; inferential, inquiry and conversational, are thought provoking and persuasive enough. It further discovered that, the artist employs some open questions so as to persuade the audience on the need to redress and change the situation. While on the other hand he employs closed rhetorical questions to effectively persuade the target audience on the prestigious nature of knowledge in the life of humankind. Finally, the paper concludes the proper and effective usage of the stylistic device in particular and the language in general